2021
DOI: 10.3390/jcm10040764
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ADAM Proteases in Bladder Cancer Patients with BCG Failure: A Pilot Study

Abstract: Although Bacillus Calmette Guérin (BCG) remains a mainstay of adjuvant treatment in high-risk, non-muscle-invasive bladder cancer, BCG failure occurs in up to 40% of patients, with radical cystectomy (RC) as the inevitable therapeutic consequence. Current data suggest that PD-L1 immunosuppressive signaling is responsible for BCG failure, supporting the therapeutic rationale of combining checkpoint inhibitors with BCG. To address the immune cascade in 19 RC specimens obtained after BCG failure, we applied a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A recent study has revealed that both ADAM10 and ADAM17 can cleave PD-L1 from the surface of malignant cells (such as 786-0 renal cell carcinoma that express both the checkpoint ligand and the two proteases) but also extracellular vesicles. ADAM proteases are considered cleavers of PD-L1 from the surface of cancer cells (e.g., bladder tumor cells) and possibly also from immune cells [ 94 ]. ADAMs, ADAM10 in particular, are known to be present in small extracellular vesicles and responsible for ectodomain shedding [ 95 , 96 ].…”
Section: Generation Of Soluble Pd-l1: Proteolysis and Alternative Splicingmentioning
confidence: 99%
“…A recent study has revealed that both ADAM10 and ADAM17 can cleave PD-L1 from the surface of malignant cells (such as 786-0 renal cell carcinoma that express both the checkpoint ligand and the two proteases) but also extracellular vesicles. ADAM proteases are considered cleavers of PD-L1 from the surface of cancer cells (e.g., bladder tumor cells) and possibly also from immune cells [ 94 ]. ADAMs, ADAM10 in particular, are known to be present in small extracellular vesicles and responsible for ectodomain shedding [ 95 , 96 ].…”
Section: Generation Of Soluble Pd-l1: Proteolysis and Alternative Splicingmentioning
confidence: 99%
“…(2021) showed a positive correlation between serum MMP-7 and sPD-L1 in patients with BUC, while Pichler et al. (2021) demonstrated an inverse correlation between mPD-L1 and ADAM17 bladder tissue expression ( 77 , 82 ).…”
Section: Discussion – Controversies Challenges and Roads To...mentioning
confidence: 98%
“…In this regard, further studies are needed since the expression of PD-L1 can be dynamic, as seen in studies that reported divergent expressions or weak correlations between mPD-L1 and sPD-L1 ( 77 , 78 ). It was shown that mPD-L1 expression correlated with the expression of metalloproteinases in both tissue and serum ( 77 , 82 ). Krafft et al.…”
Section: Discussion – Controversies Challenges and Roads To...mentioning
confidence: 99%
“…Studies related to factors that can predict the effectiveness of BCG treatment in bladder cancer have been conducted. Pichler et al [ 51 ] performed immunohistochemical staining with PD-L1, GATA-3, IL10/IL-10 receptor, and a disintegrin and metalloproteinase (ADAM) protease from radical cystectomy specimens after BCG failure. They reported that the expression of ADAM17, which has been reported to release membrane-bound PD-L1, is high in tumor regions.…”
Section: Future Strategies For Nephron-sparing Approachesmentioning
confidence: 99%